Influence of TiB2 content on the properties of TiC–SiCw composites. Issue 6 (15th April 2020) - Fattahi, Mehdi; Pazhouhanfar, Yaghoub; Delbari, Seyed Ali; Shaddel, Shahrzad; Sabahi Namini, Abbas; Shahedi Asl, Mehdi
Abstract: The impact of various volume percentages of TiB2 additive (0, 10, 20, and 30) on the microstructure, relative density (RD), Vickers hardness, flexural strength, and thermal conductivity of as-sintered TiC-10 vol% SiCw -based composite samples were scrutinized. All four samples were sintered using the SPS method under the following circumstances; sintering temperature of 1900 °C, dwell time of 7 min, and external pressure of 40 MPa. The best relative density of 98.73% was achieved for the sample with no TiB2 additive, indicating the negative effect of TiB2 additive on the RD and formation of porosity. The microstructural observations and XRD results confirmed the chemical interaction of TiO2 and B2 O3 oxide layers and SiCw and in-situ formation of the TiSi brittle phase and TiC. The most significant values of flexural strength (511 MPa) and hardness (27.67 GPa) were related to TiC-10 vol% SiCw and TiC-10 vol% SiCw -30 vol% TiB2 samples, respectively. On the contrary, the specimens with 30 vol% and 10 vol% TiB2 as additive presented the poorest qualities of flexural strength (234 MPa) and Vickers hardness (22.12 GPa). Finally, the influence of the TiB2 content on the thermal conductivity was evaluated, indicating the positive impact of this secondary phase on this characteristic, so with adding 30 vol% TiB2 to TiC-10 vol% SiCw, a thermal conductivity of 30.7 W/m.K was obtained.